2015
DOI: 10.4322/acr.2015.030
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac sarcoidosis with severe involvement of the right ventricle: a case report

Abstract: We present the case of a patient who underwent cardiac transplantation with the diagnosis of idiopathic dilated cardiomyopathy. Once the explanted heart was examined, a type of granulomatous myocarditis compatible with cardiac sarcoidosis was observed. However, there was severe involvement of the right ventricle, with markedly reduced width of the muscular layer and extensive fibrofatty replacement, findings similar to the ones encountered in cases of arrhythmogenic right ventricular cardiomyopathy (ARVC). Con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 41 publications
1
3
0
Order By: Relevance
“…Although the fibrogenic pathways are different in CS and MI ( 2 , 40 ), in the absence of data on the electrophysiologic properties of this region in CS, we assumed that it might exhibit similarly slowed conduction and decreased anisotropy. In support of this assumption, we note that gap junction lateralization, which results in slowed conduction and decreased anisotropy, has been observed histologically in fibrotic regions of human heart tissue from patients with CS ( 42 ). In addition, Muser et al ( 16 ) observed that areas of both fibrosis and inflammation in CS typically have abnormal unipolar voltage and either normal or abnormal bipolar voltage on electroanatomic maps, which further supports our assumption.…”
Section: Methodssupporting
confidence: 73%
“…Although the fibrogenic pathways are different in CS and MI ( 2 , 40 ), in the absence of data on the electrophysiologic properties of this region in CS, we assumed that it might exhibit similarly slowed conduction and decreased anisotropy. In support of this assumption, we note that gap junction lateralization, which results in slowed conduction and decreased anisotropy, has been observed histologically in fibrotic regions of human heart tissue from patients with CS ( 42 ). In addition, Muser et al ( 16 ) observed that areas of both fibrosis and inflammation in CS typically have abnormal unipolar voltage and either normal or abnormal bipolar voltage on electroanatomic maps, which further supports our assumption.…”
Section: Methodssupporting
confidence: 73%
“…An autopsy series reported left ventricular involvement in 98% and right ventricular involvement in 39% of individuals. 4,5 Reports of sarcoidosis isolated to the right ventricle based upon pathologic examination do exist. 6 FDG PET/CT is an effective tool for the diagnosis of cardiac sarcoidosis.…”
Section: Figure 2 Fdg Pet Mip (A) and Pet Axial Image Through The Hea...mentioning
confidence: 99%
“…Right ventricular disease does occur but almost always in conjunction with left ventricular sarcoidosis. An autopsy series reported left ventricular involvement in 98% and right ventricular involvement in 39% of individuals 4,5 . Reports of sarcoidosis isolated to the right ventricle based upon pathologic examination do exist 6 .…”
mentioning
confidence: 99%
“…Diagnosis requires a multi-modality evaluation and is established by fulfillment of the Revised 2010 International Task Force Criteria (TFC) 3 . Although constituting the current diagnostic gold standard, previous studies suggest that the TFC are not very specific for ARVC, and that the TFC cannot reliably differentiate between hereditary ARVC and some of its phenocopies [4][5][6][7][8] .…”
Section: Introductionmentioning
confidence: 99%